Differences in excess mortality by recipient sex after heart transplant: an individual patient data meta-analysis - Vinson, Amanda J.; Zhang, Xun; Dahhou, Mourad; Süsal, Caner; Döhler, Bernd; Melk, Anette; Sapir-Pichhadze, Ruth; Cardinal, Heloise; Wong, Germaine; Francis, Anna; Pilmore, Helen; Grinspan, Lauren T.; et al. (The journal of heart and lung transplantation, 2024)
Background - Identification of differences in mortality risk between female and male heart transplant recipients may prompt sex-specific management strategies. Because worldwide, males of all ages have higher absolute mortality rates than females, we aimed to compare the excess risk of mortality (risk above the general population) in female vs male heart transplant recipients. - Methods - We used relative survival models conducted separately in SRTR and CTS cohorts from 1988-2019, and subsequently combined using 2-stage individual patient data meta-analysis, to compare the excess risk of mortality in female vs male first heart transplant recipients, accounting for the modifying effects of donor sex and recipient current age. - Results - We analyzed 108,918 patients. When the donor was male, female recipients 0-12 years (Relative excess risk (RER) 1.13, 95% CI 1.00-1.26), 13-44 years (RER 1.17, 95% CI 1.10-1.25), and ≥45 years (RER 1.14, 95% CI 1.02-1.27) showed higher excess mortality risks than male recipients of the same age. When the donor was female, only female recipients 13-44 years showed higher excess risks of mortality than males (RER 1.09, 95% CI 1.00-1.20), though not significantly (p = 0.05). - Conclusions - In the setting of a male donor, female recipients of all ages had significantly higher excess mortality than males. When the donor was female, female recipients of reproductive age had higher excess risks of mortality than male recipients of the same age, though this was not statistically significant. Further investigation is required to determine the reasons underlying these differences.
Online verfügbar: 24. März 2024, Artikelversion: 30. Mai 2024
Gesehen am 29.11.2024